Phytochemical Screening and Biological Activity of Mentha × piperita L. and Lavandula angustifolia Mill. Extracts - Ersilia Alexa; Corina Danciu; Isidora Radulov; Diana Obistioiu; Renata Maria Sumalan; Adriana Morar; Cristina Adriana Dehelean (Analytical Cellular Pathology)
The present study aimed to investigate the phytochemical composition of Mentha × piperita L. (MP) and Lavandula angustifolia Mill. (LA) extracts in terms of hydroxycinnamic acid (HCAs) content, in particular, caffeic (CA), p-cumaric (CU), ferulic (FE), and rosmarinic (RS) acids using LC-MS. Also, the in vitro antimicrobial effect against Staphylococcus aureus and the antiproliferative activity against two cancerous cell lines (A375 and MDA-MB-231) using the MTT assay were tested. The extracts were prepared using aromatic water which resulted from the extraction of oils from plants as extraction medium, with/without acid. The results showed that RS and FE represent the majority of HCAs compounds; the highest content of FE is found in LA (7.47 mg·g–1d.m.), and the maximum content of RS in MP (6.36 mg·g–1d.m.). Regarding the antimicrobial effect against Staphylococcus aureus, the two extracts showed a simulative role on the growth rate of Staphyloccocus aureus, but a slightly inhibitory effect (69.12%) can be attributed to the acidic environment. In terms of biological activity against MDA-MB-231 breast carcinoma cell line, and A375 human melanoma cell line, at the highest employed concentration, 150 μg·mL–1, the tested extracts present a weak antiproliferative effect.